Government Support In Implementing Permenkes No. 30 / 2013 - Hari Wahono, Agus (Pusat Publikasi Nusantara, 2023)
ABSTRACT Food is a primary need for humans and is mandatory to fulfill it. Without food, humans cannot survive because food is a source of energy for humans to carry out their daily activities. To maintain our health, we also need to consume healthy foods and avoid foods that can cause various diseases. Regulation of the Minister of Health Number 30 of 2013 concerning the Inclusion of Information on Sugar, Salt, and Fat Content and Health Messages on Processed Foods and Ready-to-Eat Foods. This research is included in qualitative research and is descriptive in nature. This study is an empirical study of laws and policies in Permenkes No. 30 of 2013. The policy for including information on sugar, salt, and fat content as well as health messages for processed food needs to be accompanied by changes to the Guidelines for Inclusion of Information on Nutritional Value on Food Labels. The food industry in Indonesia can carry out a policy of including information on sugar, salt, and fat content as well as health messages for processed food. But to implement it, the food industry offers a public-private partnership model, namely the Public Health Responsibility Deal as has been done in the UK. and the Millan Declaration in Switzerland.